Liquid jet instabilities in acoustically modulated crossflow - Santos Nunez , C. (Cranfield University, 2005)
Combustion acoustic noise is a phenomenon which has attracted the attention of many people during centuries who observed the characteristics of singing flames in different conditions. It is only in recent years, with the advent of stringent environmental regulations to control combustion emissions that combustion instabilities have attracted new interest. This increasing interest is related to Lean Premixed Combustion, identified as the most promising technology for reducing NOx emissions, presents stability problems and combustion acoustic noise. Despite the adverse impact on noise and vibration affecting the combustor life, acoustic noise provokes an inefficient and unsteady combustion that generates environmental pollution. This work is related to the study of liquid jet injection under the actions of induced pressure oscillations as occurred in acoustic combustion noise. The main objective is to reproduce and analyse the coupling instability perturbations in a single liquid jet in crossflow. A test rig was design with an integrated pressure generator to produced fluctuations throughout the entire measurement range of interest. This pressure generator is a novel design that provides steady sinusoidal wave perturbations at low frequencies. Two different optical techniques were applied to measure the airflow velocity distribution as well as fuel distribution in response to the interacting acoustic oscillations. Alternatively, a mathematical model based on the laws of motion was developed to predict the jet trajectory and these predictions were compared to empirical correlations found in the literature. Empirical correlations were applied to predict the jet response and to extract relevant information with a parametric analysis. III The results show that, with the momentum flux ratio parameter that defines the jet penetration, droplet formation is governed by the time breakup. The phase lag, jet response and spray distribution are all sensitive to the magnitude of the airflow oscillations, having distinguished two groups of frequencies, crest and trough frequencies, which are related to a high and low pressure amplitude respectively.